2005
DOI: 10.1038/sj.cdd.4401586
|View full text |Cite
|
Sign up to set email alerts
|

Farnesylated RhoB inhibits radiation-induced mitotic cell death and controls radiation-induced centrosome overduplication

Abstract: Our previous results demonstrated that expressing the GTPase ras homolog gene family, member B (RhoB) in radiosensitive NIH3T3 cells increases their survival following 2 Gy irradiation (SF2). We have first demonstrated here that RhoB expression inhibits radiation-induced mitotic cell death. RhoB is present in both a farnesylated and a geranylgeranylated form in vivo. By expressing RhoB mutants encoding for farnesylated (RhoB-F cells), geranylgeranylated or the CAAX deleted form of RhoB, we have then shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Enhancement of the efficacy of 5-fluorouracil against pancreatic tumors by methionine stress is supported by the observed down-regulation of TYMS, DTYMK, and UP, which are involved in 5-fluorouracil metabolism, and FEN1, FANCG, and RAD23B, which are involved in the repair of 5-fluorouracil-induced DNA damage (45). Enhancement of the efficacy to radiation by methionine stress is supported by the observed down-regulation of RhoB expression, the farnesylated form of which inhibits radiation-induced mitotic cell death (46). Synergy between methionine stress and alkylating agents has been shown in the past (14) but has not been fully investigated.…”
Section: Discussionmentioning
confidence: 62%
“…Enhancement of the efficacy of 5-fluorouracil against pancreatic tumors by methionine stress is supported by the observed down-regulation of TYMS, DTYMK, and UP, which are involved in 5-fluorouracil metabolism, and FEN1, FANCG, and RAD23B, which are involved in the repair of 5-fluorouracil-induced DNA damage (45). Enhancement of the efficacy to radiation by methionine stress is supported by the observed down-regulation of RhoB expression, the farnesylated form of which inhibits radiation-induced mitotic cell death (46). Synergy between methionine stress and alkylating agents has been shown in the past (14) but has not been fully investigated.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, RhoB-GG suppresses Ras transformation in NIH 3T3 cells while RhoB-F potentiates transformation [9]. In contrast, RhoB-F can provide resistance to radiation-induced cell death in NIH 3T3 cells while RhoB-GG does not provide such protection [34]. The precise signaling activities that mediate these differences in signaling potential have not been delineated.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study Milia et al showed that RhoB-F (but not RhoB-GG) is required to confer resistance to radiation-induced mitotic cell death in mouse embryonic fibroblasts and that this function is dependent on ROCK I [34]. In addition, ROCK I has been reported to mediate thrombininduced NF-κB activation in endothelial cells, which in part can be attributed to increased phosphorylation of the transactivation domain of RelA/p65 [35].…”
Section: Rhob Activates Nf-κb In a Rock-dependent Mannermentioning
confidence: 99%
“…As expected, FGFR1 was silenced in the two selected U87 clones [clones 2 and 7; FGFR1(À)U87 cells], which present a significant FGFR1 inhibition of 67.1% and 38.1%, respectively ( We then deciphered the biological pathways sustaining the radioprotective effect of FGFR1 in glioblastoma cells. Because we largely demonstrated that the radiation-induced cell death of solid tumor cells is mitotic cell death (6,11,21,22), we first determined the number of giant multinucleated cells 5 days after 8 Gy irradiation when FGFR1 has been silenced or not. As shown in Fig.…”
Section: Fgfr1 Inhibition Increases the Glioblastoma Cells Sensitivitmentioning
confidence: 99%
“…The number of centrosomes in U87 and LN18 cells was analyzed using immunofluorescence staining for g-tubulin as already described (11,22).…”
Section: Evaluation Of the Centrosomes Duplicationmentioning
confidence: 99%